THE ROLE OF JOB SATISFACTION AND PERFORMANCE THROUGH COMPENSATION AND JOB ROTATION - Yohni Anwar; Wisnu Dewanto (Universitas Kristen Indonesia Toraja, 2022)
Destination study that is knowing role satisfaction in mediate compensation and rotation work to performance employee . Method analysis in study this use approach structural Equation Modelling (SEM). The population in this study are employees at outlets Indosat Ooredoo as many as 120 people . Sample research data this is taken based on sample census , that is all population made as sample that is as many as 120 respondents . Data used is the primary data where respondent get data for questionnaire . Whereas method data collection used in study this is with questionnaires and interviews . kindly direct competence and rotation work as well as satisfaction work take effect significant to performance employee whereas compensation no significant to performance employee . kindly no direct satisfaction have role significant in mediate competency and compensation to performance employee whereas satisfaction work no have role in mediate rotation work to performance employee .